Analysis of environmental impact caused from diesel passenger cars in Tirana district by using PEMS method: cases of Lancia and Citroen - Malka, Lorenc; Dhoska, Klodian (International Journal of Scientific Reports, 2016)
Background: Road transportation is the major fuel consumer and greenhouse gas emitter in the Tirana district. Emission and fuel consumption estimation models play a key role in the evaluation of the environmental emission impact caused from diesel passenger cars. Tirana as a metropolitan city of Albania is facing a serious problem that continues to be critical for the high uncontrolled level of pollution caused from this sector. Hydrocarbons (HC), Carbon dioxide (CO2) and Nitrogen oxides (NOx) are important pollutants caused by internal combustion diesel engine which simultaneously influence in ambient air quality. Analysis of the environmental impact in Tirana district for measuring HC, NOx and CO2 were briefly described in this paper. Methods: The emission level of the diesel passenger cars was measured by using E8500 gas analyser device in Tirana District. Emissions were measured over urban zone and extra urbane highway Tirana-Durrës, in total more than 50 hours of operation and 500 kilometers driven. Results: The values outside of the optimal speeds simultaneously increase the CO2 by increasing the fuel consumption and vice versa. The HC and NOx content is increased by increasing the speed regime. Conclusions: This study can be concluded that various factors influence the emission level of HC, NOx, CO2 and the use of average speed is the explanatory variable which is insufficient for estimating cars fuel consumption and especially HC and NOx emissions.